ТЕКСТ ЯК ОСНОВНА ФОРМА КОНТРОЛЮ ЗНАНЬ СТУДЕНТІВ В РАМКАХ КРЕДИТНО-МОДУЛЬНОЇ СИСТЕМИ НАВЧАННЯ (Педагогіка вищої та середньої школи, 2022)
The article deals with some peculiarities in using testcontrol as the means o f mostly objective grading o f students' knowledge.